DETERMINATION AND CORRECTION OF PROCRASTINATION IN ADULTS - Kolomiiets, Lesia; Shulga, Galyna; Lebed, Iuliia; Kharchuk, Viktor (Personality and environmental issues, 2024)
The article presents the findings of empirical and theoretical research on adult procrastination and its contributing elements. It is said that the issue of personal procrastination holds a significant position in scientific research conducted by both domestic and international scientists. The desire to explain the characteristics of an individual's functioning in a variety of, especially unstable, life circumstances is what drives this. Adult procrastination is defined as delaying actions even when one is aware that there may be unfavourable outcomes. Adults who procrastinate are more likely to experience unpleasant emotional states, as well as changes in their motivation system, self-attitude, and self-regulation. According to the analysis of the empirical study's findings, a sizable percentage of adults have a propensity to put off starting activities in order to finish planned tasks on time, are willing to wait until deadlines to begin work, and struggle to establish priorities and urgency for ongoing tasks. People in their middle adult years are more likely to postpone; women in this stage of life are more likely than men to do so. Adult procrastination has been linked to a number of elements, including situational and personal anxiety, achievement motivation, self-efficacy, self-esteem, and perfectionism. According to correlation analysis, the characteristics under study had an impact on adults' procrastination levels (p < 0.01, p ≤ 0.05). We conclude that persons who exhibit symptoms of perfectionism, significant situational and psychological anxiety, and a decline in achievement desire to avoid failures are more likely to procrastinate. Adults with low self-esteem and low self-efficacy are more likely to procrastinate. The integration of psychological education, training, and correction exercises (mini-lectures, presentations, brainstorming, group discussions, game activities, projective and art-therapeutic techniques, etc.) forms the basis of the system for correcting the factors that contribute to adult procrastination. It is decided whether it is reasonable to base a correctional system on the concepts of complexity, consistency, and systematicity while accounting for the unique requirements and traits of adults.